ANALYSIS OF INSTAGRAM ONLINE PROMOTION STRATEGIES FOR BAKSO ACI MASJAY AND BAKSO ACI GANTENG IN BANDUNG - Nur Alim, Muhammad Iqbal; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2018)
Abstract. Since 2012, Bandung city has been increasingly visited by people from various regions. It gave a great opportunity for the people of Bandung to run a culinary business. It has an impact on competition in the culinary business is also increasing. To face this issues, every culinary business must be able to maximize the promotion strategy. Promotion is very important for business as a means to building brand awareness, attracting consumers to buy products, and educating consumers. Promotions can be done in various ways, that is offline promotion and online promotion. At present, people are more interested to online promotion on social media because it is easily accessible and can reduce promotional costs. Among the many examples of social media platform, Instagram become the most popular because its users are dominated by younger-demographic users. This pushes the attention of business people to use Instagram as their online promotion strategy. Examples of culinary businesses that use Instagram as an online promotion media are Bakso Aci Masjay, but Bakso Aci Masjay has not utilized their online promotion strategy as maximal, thus making the online promotion strategy of this culinary business to be inferior from the competitor, namely Bakso Aci Ganteng.Keywords: Online Promotion Strategies, Social Media, Instagram, Bakso Aci Masjay, Bakso Aci GantengÂ